Surface-modified lithium-rich positive electrode material, positive electrode plate as well as preparation method and application of surface-modified lithium-rich positive electrode material

By forming a lithium salt cladding layer and a spinel structure transition layer on the surface of the lithium-rich positive electrode material matrix, the voltage attenuation and cyclic stability of the lithium-rich manganese-based positive electrode material in lithium-ion batteries is solved, and lithium ion transport is improved in solid-state batteries, achieving electrochemical performance with high energy density and long cycle life.

CN119725457AActive Publication Date: 2025-03-28INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411909114.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have voltage attenuation, poor cycle stability, safety problems in lithium-ion batteries, and the interface lithium-ion transport between solid-state batteries and solid electrolytes are hindered, limiting their application.

Method used

By forming a lithium salt cladding layer and a spinel structure transition layer on the surface of the lithium-rich positive electrode material matrix, the surface structure is optimized and adjusted to enhance the electrochemical performance of the material.

Benefits of technology

It significantly improves the high voltage cycle stability, rate performance, cycle life, specific capacity and energy density of lithium-rich cathode materials, and is suitable for lithium-ion batteries and solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725457A_ABST
    Figure CN119725457A_ABST
Patent Text Reader

Abstract

The invention relates to a surface-modified lithium-rich positive electrode material, a positive electrode plate as well as a preparation method and application of the surface-modified lithium-rich positive electrode material. The surface-modified lithium-rich positive electrode material comprises a lithium-rich positive electrode material matrix, a lithium salt coating layer and a spinel structure transition layer, wherein the lithium salt coating layer and the spinel structure transition layer are generated through an in-situ reaction; the spinel structure transition layer is positioned between the lithium-rich positive electrode material matrix and the lithium salt coating layer; the lithium salt coating layer is generated through an in-situ reaction of an aluminum salt and a lithium raw material; wherein the lithium raw material comprises lithium oxide and / or a material capable of generating lithium oxide through thermal decomposition, and the lithium salt coating layer is generated through in-situ reaction of lithium oxide and aluminum salt; lattices of the spinel structure transition layer and the lithium salt coating layer on the surface of the lithium-rich manganese-based positive electrode material substrate contain an element A in concentration gradient distribution, and the element A is combined with an element O to form an element A-O bond. Through surface modification, the lithium-rich positive electrode material not only has excellent lattice oxygen stability under high voltage, but also shows good lithium ion diffusivity and electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to a surface-modified lithium-rich positive electrode material, a positive electrode sheet, and a preparation method and application thereof. Background Art

[0002] In recent years, the development of electric vehicles, electric ships, and electric aircraft industries has put forward higher requirements for lithium-ion batteries, and the demand for lithium-ion batteries with high specific energy, long life, low cost, and high safety has become increasingly urgent. Lithium-ion battery positive electrode materials are key materials for improving battery energy density, and solid-state batteries are the main way to achieve high energy density batteries. Therefore, it is particularly important to develop high energy density lithium-ion battery positive electrode materials and realize solid-state lithium batteries.

[0003] Lithium-rich manganese-based layered oxides (LRMs) materials have a unique redox process, which can provide a discharge capacity of more than 300 mAh / g, and the material is currently attracting much attention. However, LRMs materials have low compaction density, voltage hysteresis, severe voltage decay and safety issues, which limit their commercial application. The irreversible redox of LRMs materials will lead to transition metal migration and a decrease in the valence state of transition metals after cycling, which is considered to be the main reason for voltage decay. In addition, the irreversible release of oxygen on the surface of LRMs materials will also lead to serious side reactions between the positive electrode and the electrolyte, affecting the safety performance and cycle stability of the battery.

[0004] So far, researchers have adopted many methods to solve the above-mentioned problems of lithium-rich manganese-based positive electrode materials: for example, adjusting the local structure and charge compensation mechanism through component optimization, coating and doping modification are all common and effective methods. Compared with cobalt-containing lithium-rich manganese-based positive electrode materials, cobalt-free lithium-rich manganese-based positive electrode materials have better voltage attenuation and cycle stability. For example, the side reaction between the surface of the positive electrode material and the electrolyte can also be reduced by constructing a surface coating protective layer. The coating materials include oxides, lithium ion conductors, phosphates, sulfides, fluorides, etc. For example, doping with foreign elements can also adjust the local oxygen environment, inhibit transition metal migration and stabilize the lattice structure. Doping elements such as cations (Al 3+ 、Ti 4+ , Nb 5+ ,La 5+ Mg 2 + ), anion (S 2- , BO4 5- PO4 3- 、SO4 2- )wait.

[0005] At present, the methods for surface modification of lithium-rich manganese-based positive electrode materials include positive electrode material surface coating, surface element doping and surface structure rearrangement, etc. However, it is difficult to completely solve the serious surface oxygen release and voltage decay problems by using the above single modification methods. Although the effect of combining the above methods is improved, it is still difficult to achieve the expected effect, and it inevitably brings about cumbersome preparation processes and serious energy consumption and economic problems.

[0006] In addition, lithium-rich manganese-based positive electrode materials are one of the preferred materials for positive electrode materials in solid-state batteries. However, due to interface problems such as solid-solid contact, the difference in the ability to conduct lithium ions between lithium-rich positive electrode materials and solid electrolytes leads to the existence of an interfacial space charge layer, which seriously affects the rapid transport of lithium ions and the capacity of the material, limiting the practical application of lithium-rich positive electrode materials in solid-state batteries.

[0007] In summary, the current surface modification of traditional lithium-rich cathode materials is difficult to completely solve the problems of severe surface oxygen release and voltage decay. Moreover, when applied to solid-state batteries, it is difficult to use them due to the large obstacles to the interfacial lithium ion transport between the lithium-rich cathode materials and the solid electrolyte, as well as the poor material kinetics and low capacity of lithium-rich manganese-based cathode materials in solid-state batteries.

[0008] Therefore, there is an urgent need for a lithium-rich positive electrode material that can combine high energy density, good cycle stability, reduced voltage decay, and high safety for lithium-ion batteries, and can be used in solid-state lithium batteries. Summary of the invention

[0009] The purpose of the present invention is to provide a surface-modified lithium-rich positive electrode material, a positive electrode sheet, and a preparation method and application thereof in view of the defects existing in the prior art. The surface-modified lithium-rich positive electrode material of the present invention has a spinel structure transition layer formed by an in-situ reaction between the lithium-rich positive electrode material matrix and the lithium salt coating layer, and a layered-spinel heterostructure is formed between the lithium-rich positive electrode material matrix, so as to optimize and adjust the surface structure of the lithium-rich positive electrode material, effectively improve the interface problem between the lithium-rich positive electrode material and the solid electrolyte, and greatly improve the electrochemical performance of the positive electrode material. When used in lithium-ion batteries, it has the advantages of excellent high-voltage cycle stability, excellent rate performance, long cycle life, high specific capacity, and high energy density.

[0010] To achieve the above objectives, in a first aspect, an embodiment of the present invention provides a surface-modified lithium-rich positive electrode material, comprising:

[0011] A lithium-rich cathode material matrix, a lithium salt coating layer generated by in-situ reaction, and a spinel structure transition layer;

[0012] The spinel structure transition layer is located between the lithium-rich positive electrode material matrix and the lithium salt coating layer;

[0013] The lithium salt coating layer is generated by an in-situ reaction between an aluminum salt and a lithium raw material; wherein the lithium raw material includes lithium oxide and / or a material that can generate lithium oxide by thermal decomposition, and the lithium salt coating layer is generated by an in-situ reaction between the lithium oxide and the aluminum salt;

[0014] The spinel structure transition layer and the lithium salt coating layer on the surface of the lithium-rich manganese-based positive electrode material substrate contain Al elements distributed in a concentration gradient in the crystal lattice, and combine with O elements to form Al-O bonds.

[0015] Preferably, the lithium-rich positive electrode material matrix is ​​a lithium-rich manganese-based positive electrode material with the chemical formula: xLi2MnO3·(1-x)LiTMO2; wherein 0≤x≤1, and TM is one or more of Ni, Co, Mn, Al, Zn, Mg, Zr, and Cr.

[0016] Preferably, the aluminum salt includes: one or more of aluminum sulfate, aluminum silicate, and aluminum sulfide;

[0017] The lithium raw material includes: one or more of lithium oxide, lithium carbonate, lithium hydroxide, and lithium acetate;

[0018] The lithium salt coating layer accounts for 0.1wt%-1wt% of the total mass of the lithium-rich positive electrode material, and the lithium salt coating layer includes: one or more of lithium sulfate, lithium silicate, and lithium sulfide.

[0019] Preferably, the material chemical formula of the spinel structure transition layer is: Li4Al y M z Mn 5-y-z O 12 ; Wherein, 0<y≤1, 0≤z≤1, and y+z≤1; M includes one or more of Ni, Co, Zn, Mg, Zr, Cr, and the thickness of the spinel structure transition layer is less than or equal to 4nm.

[0020] Preferably, the Al element accounts for 0.1%-1% of all atomic percentages of the lithium-rich manganese-based positive electrode material.

[0021] In a second aspect, an embodiment of the present invention provides a method for preparing the surface-modified lithium-rich positive electrode material described in the first aspect, comprising:

[0022] The lithium raw material, the lithium-rich positive electrode material matrix precursor and the aluminum salt are mixed and ball-milled according to the required mass ratio;

[0023] The product obtained by mixed ball milling is sintered at a high temperature of 800° C. to 900° C. for 5 to 12 hours to obtain the surface-modified lithium-rich positive electrode material.

[0024] Preferably, the lithium raw material includes: one or more of lithium oxide, lithium carbonate, lithium hydroxide, and lithium acetate;

[0025] The material chemical formula of the lithium-rich positive electrode material matrix precursor is Ni a Co b Mn c M 1-a-b-c CO3, where 0≤a≤0.45, 0≤b≤0.16, 0.39≤c≤1;

[0026] The aluminum salt includes: one or more of aluminum sulfate, aluminum silicate, and aluminum sulfide;

[0027] Before the high-temperature sintering, the method further comprises: pre-sintering the mixed ball-milled product at a temperature lower than 800° C. at a low temperature.

[0028] Preferably, the material chemical formula of the lithium-rich positive electrode material matrix precursor is preferably Ni m Mn 1-m CO3, 0.25≤m≤0.45.

[0029] In a third aspect, an embodiment of the present invention provides a positive electrode plate, comprising: the surface-modified lithium-rich positive electrode material described in the first aspect above, or the surface-modified lithium-rich positive electrode material prepared by the preparation method described in the second aspect above.

[0030] In a fourth aspect, an embodiment of the present invention provides a lithium battery, comprising: the surface-modified lithium-rich positive electrode material described in the first aspect, or the surface-modified lithium-rich positive electrode material prepared by the preparation method described in the second aspect, or the positive electrode sheet described in the third aspect;

[0031] The lithium battery includes any one of a liquid lithium ion battery, a liquid metal lithium battery, a hybrid solid-liquid lithium ion battery, a hybrid solid-liquid metal lithium battery, an in-situ solid-state lithium battery, a solid-state lithium ion battery and a solid-state metal lithium battery.

[0032] The surface-modified lithium-rich positive electrode material provided in the embodiment of the present invention has a lithium salt coating layer generated by an in-situ reaction on the surface of the lithium-rich positive electrode material matrix, and a spinel structure transition layer formed by an in-situ reaction between the lithium-rich positive electrode material matrix and the lithium salt coating layer, thereby forming a layered-spinel heterostructure between the lithium-rich positive electrode material matrix. The surface-modified lithium-rich positive electrode material of the present invention has both surface aluminum element doping, surface rearrangement and interface coating, realizes the optimization and adjustment of the surface structure of the lithium-rich positive electrode material, effectively improves the interface problem between the lithium-rich positive electrode material and the solid electrolyte, and can greatly improve the electrochemical performance of the positive electrode material. The lithium-rich positive electrode material of the present invention has the advantages of excellent high-voltage cycle stability, excellent rate performance, long cycle life, high specific capacity and high energy density when used in lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Transmission electron microscope (TEM) images of the positive electrode materials of Example 1 and Comparative Example 1 of the present invention;

[0034] Figure 2 The scanning transmission electron microscope (STEM) images of the positive electrode materials of Example 1 and Comparative Example 1 of the present invention are shown;

[0035] Figure 3 is an X-ray diffraction (XRD) diagram of the positive electrode material corresponding to Example 1 of the present invention;

[0036] Figure 4 X-ray photoelectron spectroscopy (XPS) diagrams of the positive electrode materials of Example 1 and Comparative Example 1 of the present invention;

[0037] Figure 5 The electrochemical data diagram of the positive electrode materials of Example 1 and Comparative Example 1 of the present invention;

[0038] Figure 6 Schematic diagram of the voltage attenuation comparison and structure of the positive electrode materials of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0040] The embodiment of the present invention provides a surface-modified lithium-rich cathode material, comprising: a lithium-rich cathode material matrix, a lithium salt coating layer generated by an in-situ reaction, and a spinel structure transition layer, wherein the spinel structure transition layer is located between the lithium-rich cathode material matrix and the lithium salt coating layer.

[0041] The matrix of the lithium-rich positive electrode material is a lithium-rich manganese-based positive electrode material, and the chemical formula is: xLi2MnO3·(1-x)LiTMO2; wherein 0≤x≤1, and TM is one or more of Ni, Co, Mn, Al, Zn, Mg, Zr, and Cr. Preferably, the lithium-rich manganese-based positive electrode material contains nickel, such as Li 1.15 Ni 0.30 Mn 0.55 O2、Li 1.2 Ni 0.13 Co 0.13 Mn0 .54 O2、Li 1.2 Ni 0.2 Mn 0.6 O2, etc. More preferably, the lithium-rich manganese-based positive electrode material contains nickel but no cobalt. The use of cobalt-free lithium-rich manganese-based positive electrode materials can greatly save costs, and after verification by the embodiments of the present invention, its first-week discharge specific capacity can reach the discharge specific energy of the cobalt-containing lithium-rich manganese-based positive electrode material, so that the cobalt-free lithium-rich manganese-based positive electrode material can take into account the requirements of high specific energy while saving costs.

[0042] The lithium salt coating layer is located on the surface of the lithium-rich positive electrode material matrix, and is generated by the in-situ reaction of aluminum salt and lithium raw material; wherein the lithium raw material includes lithium oxide and / or a material that can generate lithium oxide by thermal decomposition, and the lithium salt coating layer is generated by the in-situ reaction of lithium oxide and aluminum salt. The aluminum salt includes: one or more of aluminum sulfate, aluminum silicate, and aluminum sulfide, preferably aluminum sulfate; the lithium raw material includes: one or more of lithium oxide, lithium carbonate, lithium hydroxide, and lithium acetate, preferably lithium carbonate.

[0043] The lithium salt coating layer includes: one or more of lithium sulfate, lithium silicate, and lithium sulfide. The lithium salt coating layer accounts for 0.1wt%-1wt% of the total mass of the lithium-rich positive electrode material, and can be any value within the above range, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%. When the content of the lithium salt coating layer is within the above range, a suitable coating layer thickness can be achieved to reduce the side reaction between the positive electrode material and the electrolyte. Too large a coating layer thickness will lead to capacity attenuation, and too small a coating layer thickness will weaken the effect of the coating. When used in liquid lithium-ion batteries, the lithium salt coating not only effectively prevents direct contact between the electrode material and the electrolyte, but also has good stability to lattice oxygen under high voltage; when used in solid-state lithium batteries such as in-situ solid-state lithium batteries, the lithium salt coating can form a lithium ion transmission bridge between the positive electrode material and the electrolyte, thereby effectively improving the ion transmission path and enhancing the lithium ion diffusion ability of the lithium-rich manganese-based positive electrode material in the solid-state battery, thereby achieving better capacity utilization.

[0044] The lithium salt coating layer is preferably lithium sulfate. In addition to playing the role of lithium salt, the coating layer material also contains aggregated sulfate anions. The aggregation of surface sulfate polyanions has a strong SO bonding ability, which can slow down the release of irreversible oxygen on the surface and the migration of transition metals, so that the coated lithium-rich positive electrode material can have good cycle stability and voltage decay rate, so that it can be better adapted to liquid lithium-ion batteries and solid-state batteries. The inventors found that by constructing a sulfate-rich polyanion environment on the surface of the lithium-rich manganese-based positive electrode material, the local oxygen environment can be stabilized to achieve the effect of reducing the release of surface oxygen. Combining the spinel structure formed on the surface can obtain a stable structure and a three-dimensional ion diffusion channel, which can effectively stabilize the surface of the lithium-rich manganese-based positive electrode material.

[0045] The general chemical formula of the spinel structure transition layer is: Li4Al y M z Mn 5-y-z O 12 ; Wherein, 0<y≤1, 0≤z≤1, and y+z≤1; M includes one or more of Ni, Co, Zn, Mg, Zr, Cr, and the thickness of the spinel structure transition layer is less than or equal to 4nm, and can be any value within the above range, such as 1nm, 2nm, 3nm, 4nm, etc. Since the thickness of the spinel transition layer is too large, the material capacity and average voltage will be attenuated, sacrificing the specific energy of the material. The present invention can control the thickness of the spinel transition layer within the above range by controlling process parameters such as the raw material ratio and the sintering temperature.

[0046] In the process of in-situ formation of lithium-rich positive electrode material matrix, spinel structure transition layer and lithium salt coating layer by reaction between lithium raw materials, lithium-rich positive electrode material matrix precursor and aluminum salt, surface doping of aluminum atoms on the surface of lithium-rich positive electrode material matrix will also occur. The spinel structure transition layer and lithium salt coating layer on the surface of lithium-rich manganese-based positive electrode material matrix contain Al elements distributed in a concentration gradient in the lattice, and the concentration gradually decreases from the surface to the core of the matrix. Gradient doping can help stabilize the surface crystal structure, reduce surface structure collapse and better maintain the rigidity of the structure. According to the atomic molar ratio, the Al element accounts for 0.1%-1% of all atomic percentages of the lithium-rich manganese-based positive electrode material, which can be any value within the above range, such as 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.008, 0.009, 0.01. When the surface doped aluminum content is within the above range, the stability of the surface lattice oxygen and structure can be achieved. Excessive doping will lead to a decrease in the specific capacity of the material. Nano-level Al doping is formed on the surface of the lithium-rich positive electrode material matrix, which can combine with the O element on the surface of the lithium-rich positive electrode material to form an Al-O bond with strong binding energy, thereby effectively stabilizing the surface lattice oxygen and avoiding problems such as phase change caused by lattice oxygen loss.

[0047] The surface modified lithium-rich positive electrode material of the present invention can achieve the three-in-one effect of aluminum doping, surface rearrangement and interface coating on the surface of lithium-rich manganese-based positive electrode materials. Among them, the doping of surface aluminum elements can stabilize the surface crystal structure and reduce structural changes, and can better maintain the rigidity of the structure. The spinel structure formed after the surface rearrangement can accelerate the diffusion capacity of lithium ions and improve the rate performance of lithium-rich manganese-based positive electrode materials. At the same time, compared with the layered structure, the spinel structure can better bind the surface lattice oxygen and reduce the release of surface oxygen. When applied to liquid lithium batteries, the surface coating layer can effectively reduce the side reactions between the positive electrode material and the electrolyte in the liquid lithium ion battery; when applied to solid-state lithium batteries, the lithium salt coating layer can form a lithium ion transmission bridge between the positive electrode material and the electrolyte, which can effectively improve the ion transmission path and enhance the lithium ion diffusion capacity of the lithium-rich manganese-based positive electrode material in the solid-state battery, so as to have better capacity.

[0048] The present invention also provides a method for preparing a surface-modified lithium-rich manganese-based positive electrode material, which can simply utilize aluminum salts such as aluminum sulfate and a precursor of a lithium-rich positive electrode material matrix and a lithium raw material in a high-temperature sintering process to achieve surface modification of lithium-rich manganese-based positive electrode materials. The present invention can realize a lithium-rich manganese-based positive electrode material matrix, a surface lithium salt coating layer, and an in-situ reaction between the two to generate a spinel heterostructure through a one-step sintering process of a lithium-rich manganese-based positive electrode material precursor, a lithium raw material, and an aluminum salt, and a gradient doping of aluminum atoms is formed on the surface of the positive electrode material, thereby obtaining a surface-modified lithium-rich positive electrode material. The preparation method can achieve the three-in-one effect of surface element doping, surface reconstruction, and surface coating through a simple one-step synthesis, reducing the operation process while achieving multiple effects. The preparation process is simple and suitable for large-scale preparation. Through the effects of surface element doping, structural rearrangement, surface coating, etc., the cycle stability and voltage decay rate of the lithium-rich positive electrode material are significantly improved, and the related kinetic properties and thermal stability of the material are also significantly improved.

[0049] The present invention also provides a positive electrode plate, comprising a surface-modified lithium-rich positive electrode material. Since the surface of the lithium-rich positive electrode material of the present invention has a special structure and composition, it is applied to existing liquid lithium-ion batteries and has very good high-voltage cycle stability, excellent rate performance, long cycle life, high specific capacity and high energy density. When applied to solid-state batteries, especially in-situ solid-state lithium batteries, it can further enhance the battery's ion transmission capability, thereby increasing the specific capacity and energy density, and obtaining a solid-state battery with excellent safety performance.

[0050] The present invention also provides a method for preparing a surface-modified lithium-rich positive electrode material, which mainly comprises the following steps:

[0051] Step 1, mixing and ball-milling the lithium raw material, the lithium-rich positive electrode material matrix precursor, and the aluminum salt according to the required mass ratio;

[0052] The lithium raw material includes one or more of lithium oxide, lithium carbonate, lithium hydroxide and lithium acetate.

[0053] Aluminum salts include: one or more of aluminum sulfate, aluminum silicate, and aluminum sulfide.

[0054] The material chemical formula of the lithium-rich cathode material matrix precursor is Ni a Co b Mn c M 1-a-b-c CO3, wherein 0≤a≤0.45, 0≤b≤0.16, 0.39≤c≤1. Further, the precursor of the lithium-rich cathode material matrix is ​​preferably a material containing Ni and not containing Co, and the chemical formula is preferably Ni m Mn 1-m CO3, 0.25≤m≤0.45.

[0055] The required mass ratio of the above raw materials can be calculated by reverse calculation according to the required product. Those skilled in the art can know how to perform the calculation.

[0056] For example, according to the preferred embodiment of the present invention, the lithium raw material lithium carbonate: the lithium-rich positive electrode material matrix precursor Ni 0.35 Mn 0.65 The required mass ratio range of CO3: aluminum salt aluminum sulfate is [0.4-0.45]: 1: [0.001-0.01]. When the ratio of the three is controlled within the above range, it can not only ensure that the lithium raw material and the aluminum salt react completely to obtain the surface coating layer lithium salt, but also ensure that the lithium raw material reacts with the precursor to generate the target lithium-rich positive electrode material matrix, and further can form a spinel structure transition layer of suitable nanometer thickness between the lithium salt coating layer and the lithium-rich positive electrode material matrix, and obtain a suitable proportion of aluminum atom surface doping. When the lithium raw material content is too high or too low, it will lead to the formation of impurities in the lithium-rich manganese-based positive electrode material. When the aluminum salt content is too high, it affects the material's gram capacity. When it is too low, it cannot form a good lithium salt surface coating effect. For different expected products and different specific raw materials selected, the mass ratio range of the raw materials used can be obtained by reverse calculation by technicians in this field using commonly used technical means in the industry.

[0057] In a preferred example, the ball milling beads in the ball milling device of the present invention are polyurethane balls, and the ball milling speed is 200-300 rpm. Of course, those skilled in the art can understand that ball milling is a commonly used technical means in the industry, and those skilled in the art can select the specific ball milling device, ball milling medium, ball milling speed, etc. to be used according to actual needs without paying creative labor.

[0058] Step 2, sintering the mixed ball-milled product at a high temperature of 800° C. to 900° C. for 5 to 12 hours to obtain a surface-modified lithium-rich positive electrode material;

[0059] Specifically, sintering can be carried out in a tubular furnace. The high-temperature sintering temperature is 800-900°C, which can be any value within the above temperature range, such as 800°C, 820°C, 860°C, 880°C or 900°C. If the sintering temperature is too high, the primary particles of the positive electrode material will be too large and affect the capacity; if the sintering temperature is too low, the lithium-rich material will have poor crystallinity and affect the electrochemical properties of the material. The sintering time is 5-12 hours, which can be any value within the above range, such as 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. Furthermore, before high-temperature sintering, it can also include: pre-calcining the product obtained by mixed ball milling at a temperature below 800°C.

[0060] The preparation process of the present invention is simple, and only one-step sintering process is used to achieve the effects of element doping, surface reconstruction, and formation of a surface coating layer on the surface of the lithium-rich positive electrode material matrix. The preparation method can form an effective protective layer on the surface of the positive electrode material. The preparation process is not only simple and easy to operate, but also can achieve excellent material properties.

[0061] The surface-modified lithium-rich positive electrode material prepared in the present invention can be used as a positive electrode of a lithium battery and applied in a variety of energy storage devices.

[0062] The positive electrode sheet is prepared by preparing the surface-modified lithium-rich positive electrode material according to the conventional process, for example, the positive electrode material of the present invention is mixed with the conductive additive (Super P) and the binder (polyvinylidene fluoride) in a mass ratio of 96:2:2, and an appropriate amount of organic solvent (N-methylpyrrolidone) is added to form a uniformly dispersed slurry. Finally, it is evenly coated on the aluminum foil current collector by a scraper, and placed in an oven for drying to obtain the positive electrode sheet.

[0063] The surface-modified lithium-rich positive electrode material obtained by the present invention has high energy density, good structural stability and excellent cycle performance, and can be applied to lithium batteries, lithium battery packs or lithium battery modules including liquid lithium ion batteries, liquid metal lithium batteries, hybrid solid-liquid lithium ion batteries, hybrid solid-liquid metal lithium batteries, in-situ solid-state lithium batteries, solid-state lithium ion batteries and solid-state metal lithium batteries, and is widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields, and also has good application prospects in large-scale energy storage systems.

[0064] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] The reagents and materials used in the following examples and comparative examples, including electrolytes, electrolyte additives, negative electrode metal lithium, etc., are all conventional reagent products obtained from commercial sources, and can also be prepared by conventional methods. If no specific experimental steps or conditions are specified in the examples, the operations or conditions of conventional experimental steps in the art are followed.

[0066] Example 1

[0067] In this example, lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.15 Ni 0.30 Mn 0.55O2 (written as xLi2MnO3·(1-x)LiTMO2 in the form of 0.35Li2MnO3·0.65LiNi 0.546 Mn 0.453 O2).

[0068] Step 1: 10 g Ni 0.35 Mn 0.65 CO3 precursor, 4.15 g lithium carbonate and 28.3 mg aluminum sulfate were added to a ball mill, polyurethane balls were added as ball mill beads in a volume ratio of 1:1, and then ball milled at 200 rpm on a planetary ball mill for 3 h and then sieved.

[0069] Step 2: Take the powder obtained in step 1 and put it into a crucible and place it in a muffle furnace. First, heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours, then heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours. Finally, heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain a lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.15 Ni 0.30 Mn 0.55 O2. According to the test, the coating amount of lithium sulfate is 0.3wt%, and through calculation, it can be known that Al accounts for 0.2% of all atoms in the lithium-rich manganese-based positive electrode material.

[0070] The materials obtained in Example 1 were subjected to transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) tests to characterize the lithium-rich manganese-based positive electrode material Li coated with lithium ion battery obtained in Example 1. 1.15 Ni 0.30 Mn 0.55 The appearance structure and specific composition of O2 are as follows: Figure 1-4 In order to conveniently indicate the corresponding materials in the figure, ANLRM is used to represent the surface-modified lithium-rich manganese-based positive electrode material Li in Example 1 of the present invention. 1.15 Ni 0.30 Mn 0.55 Meanwhile, NLRM is used to represent the lithium-rich manganese-based positive electrode material of Comparative Example 1 of the present invention.

[0071] Example 2

[0072] In this example, lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.15 Ni 0.30 Mn 0.55 O2 (written as xLi2MnO3·(1-x)LiTMO2 in the form of 0.35Li2MnO3·0.65LiNi 0.546 Mn 0.453 O2).

[0073] Step 1: 10 g Ni 0.35 Mn 0.65 A CO3 precursor, 4.15 g of lithium carbonate and 56.6 mg of aluminum sulfate were added to a ball mill, and polyurethane balls were added as ball mill beads in a volume ratio of 1:1. The mixture was then ball milled at 200 rpm for 3 h on a planetary ball mill and sieved.

[0074] Step 2: Take the powder obtained in step 1 and put it into a crucible and place it in a muffle furnace. First, heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours, then heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours, and finally heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain a lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.15 Ni 0.30 Mn 0.55 O2. According to the test, the coating amount of lithium sulfate is 0.6wt%, and through calculation, it can be known that the percentage of Al atoms in all atoms of the lithium-rich manganese-based positive electrode material is 0.4%.

[0075] Example 3

[0076] In this example, lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 (written as xLi2MnO3·(1-x)LiTMO2 in the form of 0.5Li2MnO3·0.5LiNi 0.33 Co 0.33 Mn 0.33 O2).

[0077] Step 1: 10 g Ni 0.16 Co 0.16 Mn 0.68 A CO3 precursor, 4.125 g of lithium carbonate and 28.3 mg of aluminum sulfate were added to a ball mill, and polyurethane balls were added as ball mill beads in a volume ratio of 1:1. The mixture was then ball milled at 200 rpm on a planetary ball mill for 3 h and then sieved.

[0078] Step 2: Take the powder obtained in step 1 and put it into a crucible and then place it in a muffle furnace. First, heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours, then heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours, and finally heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54O2. According to the test, the coating amount of lithium sulfate is 0.3wt%, and through calculation, it can be known that the percentage of Al atoms in all atoms of the lithium-rich manganese-based positive electrode material is 0.17wt%.

[0079] Example 4

[0080] Lithium sulfate coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2 (written as xLi2MnO3·(1-x)LiTMO2 in the form of 0.5Li2MnO3·0.5LiNi 0.5 Mn 0.5 O2).

[0081] Step 1: 10 g Ni 0.25 Mn 0.75 CO3 carbonate precursor, 4.21 g lithium carbonate and 28.3 mg aluminum sulfate were added to a ball mill, polyurethane balls were added as ball mill beads in a volume ratio of 1:1, and then ball milled at 200 rpm on a planetary ball mill for 3 h and then sieved.

[0082] Step 2: Take the powder obtained in step 1 and put it into a crucible and then place it in a muffle furnace. First, heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours, then heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours, and finally heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain lithium sulfate-coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2. According to the test, the coating amount of lithium sulfate is 0.3wt%, and through calculation, it can be known that the percentage of Al atoms in all atoms of the lithium-rich manganese-based positive electrode material is 0.18%.

[0083] Comparative Example 1

[0084] Step 1: 10 g Ni 0.35 Mn 0.65 The CO3 precursor and 4.15 g of lithium carbonate were added to a ball mill jar, and polyurethane balls were added as ball mill beads in a volume ratio of 1:1. The mixture was then ball milled at 200 rpm on a planetary ball mill for 3 h and then sieved.

[0085] Step 2: Take the powder obtained in step 1 and put it into a crucible and place it in a muffle furnace. First, heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours, then heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours, and finally heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain the original uncoated lithium-rich manganese-based positive electrode material Li 1.15 Ni 0.30 Mn0.55 O2.

[0086] Comparative Example 2

[0087] Step 1: 10 g Ni 0.16 Co 0.16 Mn 0.68 The CO3 precursor and 4.125 g of lithium carbonate were added to a ball mill, and polyurethane balls were added as ball mill beads in a volume ratio of 1:1. The mixture was then ball milled at 200 rpm for 3 h on a planetary ball mill and sieved.

[0088] Step 2: Take the powder obtained in step 1 and put it into a crucible and place it in a muffle furnace. First, heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours. Then, heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours. Finally, heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain the original uncoated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0089] Comparative Example 3

[0090] Step 1: 10 g Ni 0.25 Mn 0.75 The CO3 precursor and 4.21 g of lithium carbonate were added to a ball mill, and polyurethane balls were added as ball mill beads in a volume ratio of 1:1. The mixture was then ball milled at 200 rpm for 3 h on a planetary ball mill and sieved.

[0091] Step 2: Put the powder obtained in step 1 into a crucible and place it in a muffle furnace. Heat it to 350°C at a heating rate of 5°C / min and keep it for 5 hours. Then heat it to 700°C at a heating rate of 5°C / min and keep it for 15 hours. Finally, heat it to 860°C at a heating rate of 5°C / min and keep it for 5 hours to obtain the original uncoated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2.

[0092] The positive electrode materials of the above-obtained embodiments and comparative examples were characterized.

[0093] Performance parameter characterization:

[0094] (I) Morphological characterization:

[0095] like Figure 1-2 As shown, the surface morphology of the positive electrode materials prepared in Example 1 and Comparative Example 1 was characterized by transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM). Figure 1Figure a is the TEM image of comparative example 1, and Figure b is the TEM image of embodiment 1. Figure 2 Figure a is a STEM image of comparative example 1, and Figure b is a STEM image of embodiment 1. It can be seen from the figure that, compared with the surface of the original material, the surface lattice structure of the lithium-rich manganese-based positive electrode material after aluminum sulfate treatment is transformed into a spinel structure, and the thickness of the spinel structure is about 2-4nm. Figure 1 As can be seen from Figure b, there is an amorphous coating layer on the outermost layer of the material of Example 1 of the present invention.

[0096] (II) Characterization of ingredients:

[0097] The coating amount of lithium salt in Example 1 of the present invention is only 0.3wt%, which is too small to characterize the composition in a general way. In order to confirm the composition of the coating material of the surface lithium-rich positive electrode material after surface modification, the coating amount of lithium sulfate in Example 1 was increased to 5wt%, that is, 10g Ni 0.35 Mn 0.65 CO3 carbonate precursor, 4.15 g lithium carbonate and 471.66 mg aluminum sulfate were prepared by the same process and characterized by XRD. The results are as follows Figure 3 As shown, characteristic peaks of lithium sulfate at 2θ=22.2° and aluminum oxide at 2θ=43.4° appeared in the synthesized sample, which indicates that the reaction products of the aluminum salt and lithium raw material in Example 1 of the present invention are lithium sulfate and aluminum oxide.

[0098] X-ray photoelectron spectroscopy (XPS) was used to analyze the surface of the positive electrode materials of Example 1 and Comparative Example 1. The results are as follows: Figure 4 As shown. Figure 4 As can be seen in a, compared with the uncoated lithium-rich manganese-based cathode material Li 1.15 Ni 0.30 Mn 0.55 O2 (NLRM in the figure), surface modified lithium-rich manganese-based positive electrode material Li 1.15 Ni 0.30 Mn 0.55 O2 (ANLRM in the figure) has a new Al-O peak at 73 eV, which proves that aluminum is doped on the surface; Figure 4 In b, the S2p spectra at different etching times also prove the presence of a sulfate coating on the surface. Figure 4 The shift of the S2p peak position in c and 4d proves that the surface-modified lithium-rich manganese-based cathode material is coated with a layer of lithium sulfate. Therefore, combined with the XPS, TEM, and STEM results, it is proved that aluminum oxide exists in the form of surface doping of the cathode material, and lithium sulfate cathode material exists in the form of a surface coating.

[0099] (III) Electrochemical performance test:

[0100] Electrochemical tests were performed on each embodiment and comparative example:

[0101] Each embodiment and comparative example is prepared as a half-cell, and the specific steps of making a button cell are as follows:

[0102] (1) The positive electrode materials obtained in Examples 1-4 and Comparative Examples 1-3 were used to prepare liquid lithium-ion batteries according to the following steps:

[0103] Preparation of the electrode sheet: According to the positive electrode material: Super P: polyvinylidene fluoride (PVDF) = 95:2.5:2.5, homogenize and coat on 20um thick aluminum foil to make a positive electrode sheet with a surface density of 4-5mg / cm 2 .

[0104] Battery assembly: button battery assembly was performed using a R2032 button battery shell, with the pole piece obtained by coating the lithium-rich manganese-based positive electrode material with lithium sulfate in Example 1-4 and the positive electrode material in Comparative Example 1-3 as the positive electrode, metallic lithium as the negative electrode, and a polyethylene (PE) diaphragm coated with aluminum oxide, and 80uL of commercial high-voltage lithium-rich electrolyte was added dropwise to obtain a button battery. The composition of the commercial high-voltage lithium-rich electrolyte is: 1 mol / L lithium hexafluorophosphate (LiPF6)@ a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (the volume ratio of EC:DEC is 1:1).

[0105] (2) The positive electrode materials obtained in Example 1 and Comparative Example 1 were used to prepare an in-situ solid-state lithium-ion battery according to the following steps:

[0106] According to the preparation process of the positive electrode plate in (1) above, the positive electrode materials of Example 1 and Comparative Example 1 are respectively prepared to obtain positive electrode plates as the positive electrode of the lithium battery, metallic lithium is used as the negative electrode, a diaphragm of PE material coated with alumina is used, and a button battery shell of R2032 is used for button assembly of solid-state batteries, and a polymerization precursor solution is injected into the battery shell. The polymerization precursor solution includes: polymerized butyl acrylate monomer, lithium salt LiTFSi, additive lithium difluorooxalate borate (LiDFOB) + succinonitrile accounting for 40wt% of the solvent mass, and initiator azobisisobutyl (AIBN) accounting for 0.5%wt of the solvent mass. Among them, the polymerized butyl acrylate monomer is 80ul, the lithium salt LiTFSi is 0.8mol / L, the additive is 0.2mol / L, and the initiator is 0.5wt%. The assembled button battery is heated in a 60℃ oven for 24h to polymerize to obtain an in-situ solid-state battery.

[0107] The lithium-ion batteries composed of the positive electrode materials of the embodiments of the present invention and the comparative examples were subjected to electrochemical charge and discharge tests:

[0108] 1) 1C cycle performance test at 30°C: Use a blue electric tester to test the button cells of the liquid batteries assembled with the positive electrode materials in Examples 1-4 and Comparative Examples 1-3. Place the prepared button cells in a high-temperature oven at 30°C for charge and discharge tests. The voltage range is 2.0V-4.8V, 0.1C charge and discharge activation for two cycles, and then constant current charge and discharge at 1C current for 500 cycles to obtain the relevant data of the first discharge capacity, first coulomb efficiency, 500th cycle discharge capacity, 500th cycle capacity retention rate, voltage retention rate and other parameters. Table 1 shows the electrochemical performance of the liquid lithium-ion batteries assembled with the positive electrode materials of each embodiment and comparative example at 1C current density at 30°C.

[0109] Table 1: Electrochemical performance at 1C current density at 30 °C.

[0110]

[0111] Figure 5 The electrochemical data diagram of the positive electrode materials of Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 6 Schematic diagram of the voltage attenuation comparison and structure of the positive electrode materials of Example 1 of the present invention and Comparative Example 1.

[0112] Combination Figure 5 and Figure 6 As shown in Table 1, it can be seen that the first discharge capacity of the positive electrode materials of Examples 1 and 2 at 0.1C is 280 mAh / g and 283 mAh / g, while the first discharge capacity of the positive electrode material of Comparative Example 1 at 0.1C is 270 mAh / g (as shown in Table 1). Figure 5 a), it can be seen that the coated positive electrode material has a higher first discharge capacity at 0.1C, wherein Example 1 and Example 2 are 10mAh / g and 13mAh / g higher than Comparative Example 1, respectively. The first discharge capacity of Examples 1-2 at 1C is 230mAh / g and 226mAh / g, while that of Comparative Example 1 is 220mAh / g. It can be seen that the discharge specific capacity of the lithium-rich manganese-based positive electrode material coated with aluminum sulfate of the present invention is increased by 10mAh / g and 6mAh / g, respectively. From the first coulomb efficiency, Examples 1-2 are 86.4% and 84.71%, respectively, both higher than 84% of Comparative Example 1. At 30°C and a current density of 1C, after 500 cycles between 2.0V-4.8V, the capacity retention rates of the positive electrode materials of Examples 1-2 are 93.58% and 90.83%, respectively, while that of Comparative Example 1 is only 87.5% (e.g. Figure 5 b). It can be seen that the capacity retention rate of the aluminum sulfate-coated lithium-rich manganese-based positive electrode material at a high voltage of 4.8V is better than that of the uncoated material. In addition, the voltage decay rate of the materials in Examples 1-2 after 500 cycles is 0.28mV / cycle and 0.42mV / cycle, while that of Comparative Example 1 is 0.58mV / cycle (as shown in Figure 2). Figure 5 c. Figure 6 ), it can be seen that the voltage decay rate of the uncoated material of Comparative Example 1 is 0.3mV / cycle higher than that of the lithium-rich material coated with aluminum sulfate in Example 1, which is 51.7% higher. Therefore, the lithium-rich manganese-based positive electrode material coated with aluminum sulfate has a very low voltage decay. The specific energy retention rate of Example 1 is 90% after 500 cycles, while the retention rate of Comparative Example 1 is only 80.5% after 500 cycles, which is an increase of 9.5% in the specific energy retention rate. Examples 1-2 of the present invention have smaller voltage decay and higher specific capacity after 500 cycles, and therefore have higher energy density. The discharge specific energy (calculated based on active materials) of the modified material in Example 1 still has a discharge specific energy of 734Wh / Kg after stable cycling for 500 cycles at a 1C cycle rate, while the discharge specific energy of Comparative Example 1 after cycling is only 633Wh / Kg, and Example 1 is 101Wh / Kg higher than Comparative Example 1. After long cycling after being coated with lithium sulfate, the material of the present invention still has a very high energy density, which will greatly enhance the competitive advantage of lithium-rich manganese-based positive electrode materials in the market. By comparing Examples 1-2 with Comparative Example 1, it can be seen that the surface-modified lithium-rich manganese-based positive electrode material of the present invention has very excellent high-voltage cycle stability and less voltage decay, because the surface of the material has a stable local oxygen environment after the lithium sulfate surface modification, which reduces the irreversible oxygen release on the surface and has better structural stability. Therefore, the lithium-rich manganese-based material prepared by this method has excellent high-voltage cycle stability, high specific capacity and energy density, which will greatly enhance the competitive advantage of lithium-rich manganese-based positive electrode materials in the market.

[0113] Example 3: 0.3 wt% lithium sulfate is used to coat the lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, Li-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54O2 does not have a lithium sulfate coating layer. It can be seen that the first discharge capacity of the positive electrode material of Example 3 at 0.1C is 296mAh / g, while the first discharge capacity of the positive electrode material of Comparative Example 2 at 0.1C is 290mAh / g. It can be seen that the first discharge capacity of the coated positive electrode material at 0.1C is higher. The first discharge capacity of Example 3 at 1C is 248mAh / g, while that of Comparative Example 2 is 250mAh / g. From the perspective of the first coulombic efficiency, Example 3 is 85.09%, while that of Comparative Example 2 is 80%, and Example 3 is significantly higher than Comparative Example 3. At 30°C and 1C current density, after 500 cycles between 2.0V-4.8V, the capacity retention rate of the positive electrode material of Example 3 is 88.57%, while that of Comparative Example 2 is only 74.76%. It can be seen that aluminum sulfate coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The capacity retention rate of O2 at a high voltage of 4.8V is superior to that of the uncoated material, which is about 13.81% higher. In addition, the voltage decay rate of the positive electrode material of Example 3 after 500 cycles is 0.88mV / cycle, while that of Comparative Example 2 is 1mV / cycle. It can be seen that the voltage decay rate of the uncoated lithium sulfate material in Comparative Example 2 is 0.12mV / cycle higher than that of Example 2, and its voltage decay is obvious. Therefore, the lithium sulfate coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 has very low voltage decay. By comparing Example 3 with Comparative Example 2, it can be seen that the surface-modified lithium-rich manganese-based positive electrode material of the present invention has very excellent high voltage cycle stability, small voltage decay, and excellent electrochemical performance by using different lithium-rich manganese-based positive electrode material matrices.

[0114] Example 4: 0.3 wt% lithium sulfate is used to coat the lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2, Li-rich manganese-based positive electrode material Li of comparative example 3 1.2 Ni 0.2 Mn 0.6O2 does not have a lithium sulfate coating. It can be seen that the first discharge capacity of the positive electrode material of Example 4 at 0.1C is 269.32mAh / g, while the first discharge capacity of the positive electrode material of Comparative Example 3 at 0.1C is 257mAh / g. The first discharge capacity of Example 4 at 1C is 217.9mAh / g, while that of Comparative Example 3 is 207.8mAh / g. It can be seen that the first discharge capacity of Example 4 at 0.1C and 1C is significantly higher than that of Comparative Example 3. At 30°C and 1C current density, after 500 cycles between 2.0V-4.8V, the capacity retention rate of the positive electrode material of Example 4 is 88.08%, while that of Comparative Example 3 is only 81.44%. It can be seen that the aluminum sulfate-coated lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 The capacity retention rate of O2 at a high voltage of 4.8V is superior to that of the uncoated material. In addition, the voltage decay rate of the positive electrode material of Example 4 after 500 cycles is 0.64mV / cycle, while that of Comparative Example 3 is 0.65mV / cycle. By comparing Example 4 with Comparative Example 3, it can be seen that the surface-modified lithium-rich manganese-based positive electrode material of the present invention has very excellent high-voltage cycle stability, small voltage decay, and excellent electrochemical performance by using different lithium-rich manganese-based positive electrode material matrices.

[0115] 2) Rate discharge performance test at 30°C: The button cells assembled with the positive electrode materials in Example 1 and Comparative Example 1 were tested using a blue electricity tester with a voltage range of 2.0V-4.8V, and constant current charge and discharge were performed at a current of 1C; constant current discharge cycles were performed for 5 weeks at currents of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, respectively, and the discharge cut-off voltage was 2.0V.

[0116] Table 2 shows the rate performance of liquid lithium-ion batteries assembled with the positive electrode materials of Example 1 and Comparative Example 1 and tested at 30°C.

[0117]

[0118] The positive electrode materials of Example 1 and Comparative Example 1 were tested for rate performance and the specific data are as follows: Figure 5d. It can be seen that the specific capacities of Example 1 after 5 weeks of constant current discharge cycles at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C currents are 275mAh / g, 258mAh / g, 241mAh / g, 226mAh / g, 206mAh / g, and 185mAh / g, respectively, while the specific capacities of Comparative Example 1 after 5 weeks of constant current discharge cycles at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C currents are 264mAh / g, 249mAh / g, 231mAh / g, 213mAh / g, 196mAh / g, and 169mAh / g, respectively. It can be seen that with the increase of current density, the gap between the specific capacities of the positive electrode materials of Example 1 and Comparative Example 1 gradually increases. At current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C, the specific capacity of Example 1 is 9-13 mAh / g higher than that of Comparative Example 1, and at a current density of 5C, Example 1 is 16 mAh / g higher than that of Comparative Example 1, which indicates that at high rates, the lithium-rich positive electrode material of the present invention has a higher specific capacity after being coated with lithium sulfate, has better rate performance, and voltage retention rate.

[0119] 3) Test of the first-week discharge specific capacity and coulombic efficiency of the in-situ solid-state battery at 0.1C at 30°C: The button cells assembled with the positive electrode materials in Example 1 and Comparative Example 1 were tested using a blue electric tester. The prepared button cells were placed in a high-temperature oven at 30°C for charge and discharge tests with a voltage range of 2.0V-4.8V and two cycles of 0.1C charge and discharge activation to obtain the first discharge capacity and the first coulombic efficiency.

[0120] Table 3 is the discharge capacity test data of the in-situ solid-state lithium-ion batteries assembled with the positive electrode materials of Example 1 and Comparative Example 1.

[0121] 0.1C discharge capacity mAh / g 1C discharge capacity mAh / g Example 1 272 229 Comparative Example 1 259 214

[0122] After the positive electrode materials obtained in Example 1 and Comparative Example 1 were assembled into an in-situ solid-state battery, the first discharge capacity of Example 1 at 0.1C was 272mAh / g, while the first discharge capacity of the positive electrode material of Comparative Example 1 at 0.1C was 259mAh / g, indicating that the first discharge capacity of the coated positive electrode material at 0.1C was 13mAh / g higher. The first discharge capacity of the in-situ solid-state battery obtained in Example 1 at 1C was 229mAh / gg, while that of Comparative Example 1 was 214mAh / g, indicating that the discharge specific capacity of the lithium-rich manganese-based positive electrode material coated with aluminum sulfate of the present invention was increased by 15mAh / g. From the in-situ solid-state battery assembled from the positive electrode materials of Example 1 and Comparative Example 1, the surface-modified lithium-rich manganese-based positive electrode material of the present invention still has a very good specific capacity when applied to solid-state batteries. This is because the coating of lithium sulfate and the positive electrode material matrix of the present invention can construct a more robust lithium ion transmission channel, and the lithium ion interface conduction between the positive electrode material and the solid electrolyte is enhanced, so that the modified lithium-rich manganese-based positive electrode material can have a more excellent lithium ion diffusion ability in the solid-state battery, thereby exerting a higher capacity.

[0123] This shows that the surface-modified lithium-rich cathode material of the present invention has both surface aluminum doping, surface rearrangement and interface coating, realizes the optimization and adjustment of the surface structure of the lithium-rich cathode material, effectively improves the interface problem between the lithium-rich cathode material and the solid electrolyte, and can greatly improve the electrochemical performance of the cathode material. The lithium-rich cathode material of the present invention has the advantages of excellent high-voltage cycle stability, excellent rate performance, long cycle life, high specific capacity and high energy density when used in lithium-ion batteries.

[0124] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A surface-modified lithium-rich cathode material, characterized in that: The surface-modified lithium-rich cathode material comprises: A lithium-rich cathode material matrix, a lithium salt coating layer generated by in-situ reaction, and a spinel structure transition layer; The spinel structure transition layer is located between the lithium-rich positive electrode material matrix and the lithium salt coating layer; The lithium salt coating layer is generated by an in-situ reaction between an aluminum salt and a lithium raw material; wherein the lithium raw material includes lithium oxide and / or a material that can generate lithium oxide by thermal decomposition, and the lithium salt coating layer is generated by an in-situ reaction between the lithium oxide and the aluminum salt; The spinel structure transition layer and the lithium salt coating layer on the surface of the lithium-rich manganese-based positive electrode material substrate contain Al elements distributed in a concentration gradient in the crystal lattice, and combine with O elements to form Al-O bonds.

2. The surface-modified lithium-rich cathode material according to claim 1, characterized in that: The lithium-rich positive electrode material matrix is ​​a lithium-rich manganese-based positive electrode material, and the chemical formula is: xLi2MnO3·(1-x)LiTMO2; Among them, 0≤x≤1, TM is one or more of Ni, Co, Mn, Al, Zn, Mg, Zr, and Cr.

3. The surface-modified lithium-rich cathode material according to claim 1, characterized in that: The aluminum salt includes: one or more of aluminum sulfate, aluminum silicate, and aluminum sulfide; The lithium raw material includes: one or more of lithium oxide, lithium carbonate, lithium hydroxide, and lithium acetate; The lithium salt coating layer accounts for 0.1wt%-1wt% of the total mass of the lithium-rich positive electrode material, and the lithium salt coating layer includes: one or more of lithium sulfate, lithium silicate, and lithium sulfide.

4. The surface-modified lithium-rich cathode material according to claim 1, characterized in that: The material chemical formula of the spinel structure transition layer is: Li4Al y M z Mn 5-y-z O 12 ; Wherein, 0<y≤1, 0≤z≤1, and y+z≤1; M includes one or more of Ni, Co, Zn, Mg, Zr, Cr, and the thickness of the spinel structure transition layer is less than or equal to 4nm.

5. The surface-modified lithium-rich cathode material according to claim 1, characterized in that: The Al element accounts for 0.1%-1% of all atomic percentages of the lithium-rich manganese-based positive electrode material.

6. A method for preparing a surface-modified lithium-rich cathode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: The lithium raw material, the lithium-rich positive electrode material matrix precursor and the aluminum salt are mixed and ball-milled according to the required mass ratio; The product obtained by mixed ball milling is sintered at a high temperature of 800° C. to 900° C. for 5 to 12 hours to obtain the surface-modified lithium-rich positive electrode material.

7. The preparation method according to claim 6, characterized in that: The lithium raw material includes: one or more of lithium oxide, lithium carbonate, lithium hydroxide, and lithium acetate; The material chemical formula of the lithium-rich positive electrode material matrix precursor is Ni a Co b Mn c M 1-a-b-c CO3, where 0≤a≤0.45, 0≤b≤0.16, 0.39≤c≤1; The aluminum salt includes: one or more of aluminum sulfate, aluminum silicate, and aluminum sulfide; Before the high-temperature sintering, the method further comprises: pre-sintering the mixed ball-milled product at a temperature lower than 800° C. at a low temperature.

8. The preparation method according to claim 7, characterized in that: The material chemical formula of the lithium-rich positive electrode material matrix precursor is preferably Ni m Mn 1-m CO3, 0.25≤m≤0.

45.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises: the surface-modified lithium-rich positive electrode material described in any one of claims 1 to 5 above, or the surface-modified lithium-rich positive electrode material prepared by the preparation method described in any one of claims 6 to 8 above.

10. A lithium battery, characterized in that: The lithium battery comprises the surface-modified lithium-rich positive electrode material according to any one of claims 1 to 5, or the surface-modified lithium-rich positive electrode material obtained by the preparation method according to any one of claims 6 to 8, or the positive electrode sheet according to claim 9; The lithium battery includes any one of a liquid lithium ion battery, a liquid metal lithium battery, a hybrid solid-liquid lithium ion battery, a hybrid solid-liquid metal lithium battery, an in-situ solid-state lithium battery, a solid-state lithium ion battery and a solid-state metal lithium battery.

Citation Information

Patent Citations

  • Preparation method of high-performance aluminum-doped lithium-rich spinel lithium manganate anode material

    CN106997949A

  • Lithium-rich positive electrode material based on surface modification of MOFs and preparation method thereof

    CN108336316A

  • Modified lithium-rich manganese-based material as well as preparation method and application thereof

    CN114335509A

  • Spinel / layered heterostructure modified cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN114671471A

  • Lithium-rich manganese-based positive electrode material and preparation method and application thereof

    CN118507700A

Cited By

  • Molybdenum disulfide and lithium lanthanum niobium oxygen co-coated lithium-rich manganese-based positive electrode material and preparation method thereof

    CN120072912A

  • Multi-modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN121687925A